2013
DOI: 10.1007/s10549-013-2559-1
|View full text |Cite
|
Sign up to set email alerts
|

Multigene assays and molecular markers in breast cancer: systematic review of health economic analyses

Abstract: Breast cancer is the most common female cancer and is associated with a significant clinical and economic burden. Multigene assays and molecular markers represent an opportunity to direct chemotherapy only to patients likely to have significant benefit. This systematic review examines published health economic analyses to assess the support for adjuvant therapy decision making. Literature searches of PubMed, the Cochrane Library, and congress databases were carried out to identify economic evaluations of multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 44 publications
0
66
0
4
Order By: Relevance
“…30,[47][48][49] However, the widespread use of this test has come into question recently, as the literature has suggested that certain cases might be risk stratified more costeffectively using histopathologic variables. [50][51][52][53][54] Our data support this.…”
Section: Modern Pathology (2015) 28 921-931mentioning
confidence: 99%
“…30,[47][48][49] However, the widespread use of this test has come into question recently, as the literature has suggested that certain cases might be risk stratified more costeffectively using histopathologic variables. [50][51][52][53][54] Our data support this.…”
Section: Modern Pathology (2015) 28 921-931mentioning
confidence: 99%
“…15 Since the publication of the evidence review and EGAPP recommendation statement, several systematic reviews have been published addressing questions relating to the clinical utility and cost-effectiveness of Oncotype DX and MammaPrint. [16][17][18][19][20] On the basis of an overview of the findings of five of these systematic reviews 21 and additional published evidence, the EWG decided to prepare an updated version of its 2009 recommendation statement. This update focuses on the Oncotype DX test.…”
Section: Background and Clinical Context For The Recommendationmentioning
confidence: 99%
“…17,18 Two additional systematic reviews 19,20 summarized results from cost-effectiveness analyses reported in the included studies. Of these, only one assessed the quality of the included studies by criteria specific for economic analyses.…”
Section: Cost-effectivenessmentioning
confidence: 99%
See 2 more Smart Citations